High-strength durable anti-drag film and preparation method thereof
By preparing a high-strength and durable drag-reducing membrane, the shortcomings of existing drag-reducing membranes in terms of high strength and durability are solved, and a stable drag-reducing effect is achieved under high-speed or high-altitude conditions.
Patent Information
- Application Number
- CN202511862051.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-11
- Publication Date
- 2026-01-16
- Estimated Expiration
- 2045-12-11
AI Technical Summary
Existing drag-reducing membranes are insufficient in terms of high strength and durability, which makes them prone to aging and breakage under high-speed or high-altitude conditions, thus weakening their drag-reducing effect.
A drag-reducing phenol-modified TPU prepolymer was prepared by using 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and isocyanate-terminated TPU prepolymer. This prepolymer was then co-extruded with CTAB-montmorillonite to form a base film. After plasma cleaning of the silicone-modified TPU surface film, a SEBS-modified polyurethane adhesive was prepared by grafting SEBS with hydroxyl-terminated polyurethane and maleic anhydride. The resulting high-strength, durable drag-reducing film was formed through hot-pressing and photothermal synergistic curing.
It improves the strength and durability of the drag-reducing film, enhances the tensile strength, heat resistance and interfacial bonding strength of the material, reduces surface energy, and improves drag reduction performance.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of drag reduction films, in particular to a high-strength durable drag reduction film and a preparation method thereof. BACKGROUND
[0002] When an object moves in a fluid, it needs to overcome the influence of resistance, including surface friction resistance, pressure difference resistance, etc. When overcoming these resistances to move, the object needs to consume additional energy. For example, aircraft, high-speed trains, ships and other transportation tools, overcoming resistance not only can reduce energy consumption such as fuel and electricity, but also can improve transportation efficiency. Traditional drag reduction technology reduces resistance through surface polishing, low surface energy coating and other methods, but still has some limitations. Although the surface polishing technology can reduce the surface roughness, it is limited by the machining precision, the processing cost is high, and the surface is difficult to maintain an ultra-smooth state for a long time under the influence of impact or erosion, so the drag reduction effect is weakened; although the low surface energy coating can reduce the surface energy, the bonding strength with the substrate is weak, and the coating is easy to fall off after long-time abrasion or environmental erosion, so the drag reduction effect is weakened.
[0003] The drag reduction film is a kind of composite film material with fine microstructure on the surface. The microstructure on the surface can direct the turbulent structure of the fluid boundary layer, so as to achieve the effect of reducing resistance. However, at present, the drag reduction film is limited by the material, and the strength is insufficient and the durability is poor. Under complex conditions such as high speed or high altitude, the film layer or microstructure is easy to age and break, resulting in failure of the drag reduction structure. Therefore, improving the strength and durability of the drag reduction film is of great importance to promote the large-scale application of the drag reduction film in high-end fields. SUMMARY
[0004] The application aims to provide a high-strength durable drag reduction film and a preparation method thereof, improve the strength and durability of the film layer and microstructure of the drag reduction film, and solve the problems of insufficient strength and poor durability of the drag reduction film.
[0005] In order to solve the above technical problems, the application provides the following technical scheme: A preparation method of a high-strength durable drag reduction film, specifically comprising the following steps: Step 1: using 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and isocyanate-terminated TPU prepolymer to prepare hindered phenol-modified TPU prepolymer, and blending and extruding with CTAB-montmorillonite to prepare a hindered phenol-MMT-TPU base film; Step 2: using hydroxyl-terminated polymethylphenylsiloxane, polytetramethylene ether glycol and isophorone diisocyanate to prepare silicone-modified TPU prepolymer, and blending and extruding with KH-560-modified titanium dioxide to prepare a silicone-modified TPU surface film; Step 3: After the plasma cleaning of the hindered phenol-MMT-TPU base film and the silicone-modified TPU surface film, a SEBS-modified polyurethane adhesive prepared by using a hydroxyl-terminated polyurethane and a maleic anhydride grafted SEBS is coated on the hindered phenol-MMT-TPU base film and dried to form an adhesive layer, and then the hindered phenol-MMT-TPU base film and the silicone-modified TPU surface film are hot-pressed to form a high-strength durable drag-reducing film.
[0006] During the plasma cleaning, the mixed gas of argon and oxygen is used, the flow rate of argon is 15-20 sccm, the flow rate of oxygen is 5-10 sccm, the plasma power is 80-100 w, and the cleaning time is 60-120 s; during the drying, the drying temperature is 80-90 DEG C, and the drying time is 10-20 min; during the hot-pressing, the hot-pressing temperature is 110-120 DEG C, the hot-pressing pressure is 0.3-0.5 MPa, and the hot-pressing time is 5-10 min; during the light-heat synergistic curing, the 365 nm ultraviolet light source is used, the curing temperature is 110-120 DEG C, and the curing time is 10-20 min.
[0007] As a limitation of the present application, the preparation method of the hindered phenol-MMT-TPU base film is as follows: Under the protection of nitrogen, the terminal isocyanate group TPU prepolymer, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol is added to butyl acetate, dissolved under 80-90 DEG C, 300-400 rpm magnetic stirring for 30-40 min, add catalyst dibutyltin dilaurate, stir evenly, reaction at 110-120 DEG C for 4-5 h, after the reaction is completed, vacuum drying at 60-70 DEG C for 6-8 h, hindered phenol modified TPU prepolymer is obtained; The hindered phenol modified TPU prepolymer, polyethylene glycol monoacrylate is added to the twin-screw extruder, the melting temperature is set to 170-180 DEG C, the screw rotation speed is 150-200 rpm, the melt blending is carried out for 3-5 min, then CTAB-montmorillonite and silane coupling agent KH-550 are added, the rotation speed is increased to 300-350 rpm, and the blending is continued for 5-10 min, then the extrusion is carried out, the peroxide is added at the end of the extruder, the extrusion temperature is 180-190 DEG C, the screw rotation speed is 200-250 rpm, and the die temperature is 170-180 DEG C, and the hindered phenol-MMT-TPU base film is obtained.
[0008] As a limitation of the present application, the mass ratio of the terminal isocyanate group TPU prepolymer, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and butyl acetate is (80-90):(5-10):(80-100), and the mass of dibutyltin dilaurate is 0.8-1.5 wt% of the mass of the terminal isocyanate group TPU prepolymer.
[0009] As defined in the present application, the hindered phenol-MMT-TPU base film includes, in parts by mass: 75-85 parts of hindered phenol modified TPU prepolymer, 1.5-2.5 parts of polyethylene glycol monoacrylate, 4-6 parts of CTAB-montmorillonite, and 1-3 parts of silane coupling agent KH-550, 0.5-1 parts of dibenzoyl peroxide; the thickness of the hindered phenol-MMT-TPU base film is 30-50 μm.
[0010] Under the action of catalyst dibutyltin dilaurate, the isocyanate group (-NCO) of the terminal isocyanate group TPU prepolymer undergoes nucleophilic addition reaction with the alcohol hydroxyl group (-OH) of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol to generate a urethane bond (-NHCOO-), the antioxidant 3,5-di-tert-butyl-4-hydroxybenzyl alcohol is connected to the TPU molecular chain through a covalent bond, the antioxidant 3,5-di-tert-butyl-4-hydroxybenzyl alcohol structure contains alcohol hydroxyl and phenolic hydroxyl, the alcohol hydroxyl preferentially binds with the isocyanate to generate a urethane bond, and the phenolic hydroxyl can capture alkoxy radicals (·RO) generated during TPU aging to block the oxidation chain growth, thereby delaying the aging process of TPU, inhibiting the oxidative degradation of TPU under high temperature conditions or in the subsequent processing process, and the benzyl alcohol group of the antioxidant interacts with the soft segment (such as PTMG) in the TPU molecular chain through van der Waals force, reducing the intramolecular aggregation of the TPU prepolymer and improving the dispersibility in the subsequent blending process.
[0011] The polyethylene glycol monoacrylate contains hydroxyl groups (-OH) and acrylate double bonds (-C=C-), the hydroxyl groups react with the residual isocyanate groups (-NCO) in the hindered phenol modified TPU prepolymer to form a urethane bond (-NHCOO-), the benzoyloxy (·OCOC6H5) radicals generated by the decomposition of BPO initiate the polymerization of the acrylate double bonds to form a three-dimensional crosslinked network, which improves the crosslinking density and enhances the tensile strength and heat resistance of the material; the silane coupling agent KH-550 condenses with the silicon hydroxyl groups (Si-OH) on the surface of the CTAB-montmorillonite to form Si-O-Si bonds, which promotes the dispersion of the CTAB-montmorillonite in the TPU, the lamellar structure of the CTAB-montmorillonite can block the diffusion of water and oxygen, slow down the aging process of the material, and improve the aging resistance of the material, the lamellar structure is physically entangled and anchored between the TPU molecular chains, which hinders the slipping of the TPU molecular chains, absorbs and disperses the tensile stress received, reduces the generation of microcracks, and improves the strength and aging resistance of the material.
[0012] As defined in the present application, the preparation method of the organic silicon modified TPU surface film is: The hydroxyl-terminated polymethylphenylsiloxane and polytetrahydrofuran ether diol are added into a reaction kettle, and are mixed at 60-70 DEG C and 100-150 rpm magnetic stirring for 20-30 min, then isophorone diisocyanate is added, the temperature is raised to 80-90 DEG C and reacted for 3-4 h, after the reaction is completed, the temperature is lowered to 40-50 DEG C, 1,4-butanediol is added, and reacted at 70-80 DEG C for 2-3 h to obtain a silicone modified TPU prepolymer; The silicone modified TPU prepolymer and KH-560 modified titanium dioxide are added into a twin-screw extruder, the screw rotation speed is set to 200-250 rpm, the melting temperature is 170-180 DEG C, and the blending time is 3-5 min, after blending is completed, antioxidant 1010 and light stabilizer 944 are added, and after 5-10 min of continuous blending, extrusion and roll pressing are carried out, dibenzoyl peroxide is added at the end of the extruder, the extrusion temperature is 180-190 DEG C, the screw rotation speed is 200-250 rpm, the die temperature is 170-180 DEG C, the roll pressing temperature is 130-140 DEG C, the roll pressing pressure is 0.3-0.5 MPa, and a silicone modified TPU surface film is obtained.
[0013] As a limitation of the application, the mass ratio of the hydroxyl-terminated polymethylphenylsiloxane, polytetrahydrofuran ether diol, isophorone diisocyanate and 1,4-butanediol is (60-70):(40-50):(8.5-9.5):(0.6-1.0).
[0014] As a limitation of the application, in the silicone modified TPU surface film, by mass parts, it includes: 70-80 parts of silicone modified TPU prepolymer, 8-12 parts of KH-560 modified titanium dioxide, 0.8-1.2 parts of antioxidant 1010, 0.5-0.7 parts of light stabilizer 944, and 0.5-1 parts of dibenzoyl peroxide; the thickness of the silicone modified TPU surface film is 30-50 microns.
[0015] The hydroxyl (-OH) of the hydroxyl-terminated polymethylphenylsiloxane and polytetrahydrofuran ether diol reacts with the isocyanate group (-NCO) of isophorone diisocyanate to form a urethane bond (-NHCOO-), forming a block prepolymer containing siloxane segments, and further through the chain extension reaction of BDO, a polyurethane long chain structure containing siloxane segments is generated, the benzene ring and siloxane segment are contained in the hydroxyl-terminated polymethylphenylsiloxane, the benzene ring as a rigid structure is introduced into the molecular chain, which can improve the heat resistance and strength of the prepolymer, and the siloxane segment improves the surface contact angle of the prepolymer, thereby reducing the surface energy of the material and improving the ultraviolet resistance and drag reduction performance of the material.
[0016] The nano-titanium dioxide is modified by silane coupling agent KH-560, and is uniformly dispersed in the TPU matrix. The modified nano-titanium dioxide is anchored in the TPU matrix by the reaction between the siloxane group and the hydroxyl group of the TPU, promotes crack deflection, improves the tensile strength of the material, and cooperates with the light stabilizer and the antioxidant to improve the weather resistance of the material. During the crosslinking process, the benzoyloxy group (·OCOC6H5) promotes the crosslinking between the TPU molecular chains, forms a three-dimensional network structure, improves the strength and heat resistance of the material, and further improves the crosslinking density by the reaction between the epoxy group of the silane coupling agent KH-560 after ring opening and the hydroxyl group (-OH) of the TPU, enhances the bonding strength between the filler and the TPU matrix, and enhances the strength and heat resistance of the material.
[0017] As a limitation of the present application, the preparation method of the SEBS modified polyurethane adhesive is: The hydroxyl-terminated polyurethane, maleic anhydride grafted SEBS and polyurethane acrylate are added to tetrahydrofuran, and are stirred at 60-70°C and 100-150rpm for 20-30min. The modified silica KH-560 is added and is ultrasonically dispersed for 5-10min. The temperature is lowered to 30-40°C, the photoinitiator TPO is added, and the stirring is continued for 10-20min. Finally, the antioxidant 1010 and the light stabilizer 944 are added and are ultrasonically dispersed for 15-20min, to obtain the SEBS modified polyurethane adhesive.
[0018] As a limitation of the present application, the SEBS modified polyurethane adhesive includes, by mass fraction: 50-60 parts of hydroxyl-terminated polyurethane, 15-20 parts of maleic anhydride grafted SEBS, 10-15 parts of polyurethane acrylate, 50-60 parts of tetrahydrofuran, 2.5-3.5 parts of modified silica KH-560, 0.8-1.2 parts of antioxidant 1010, and 0.5-0.7 parts of light stabilizer 944.
[0019] The adhesive contains hydroxyl-terminated polyurethane and maleic anhydride grafted SEBS, the hydroxyl-terminated polyurethane has good compatibility with the base film and the surface film, after plasma cleaning, the impurities adhered in the film surface processing process are removed, the highly crosslinked part of the film surface is etched by plasma, the active functional groups such as hydroxyl (-OH) and carboxyl (-COOH) in the interior are released, the oxygen free radicals react with the broken bonds on the film surface, the surface forms oxygen-containing active groups, the interfacial bonding strength of the adhesive and the film is enhanced, in the hot pressing and compounding process, the maleic anhydride grafted SEBS diffuses to the interface of the base film and the surface film, the anhydride groups (-CO-O-CO-) in the structure condense with the hydroxyl groups (-OH) on the base film and the surface film to form ester bonds (-COO-), and the two synergistically enhance the interfacial bonding strength, in the curing process, the benzoyloxy groups (·OCOC6H5) promote the crosslinking of the acrylate groups double bonds at the molecular ends of the polyurethane acrylate, form a three-dimensional crosslinked network, and improve the peeling strength and heat resistance of the material.
[0020] A high-strength durable drag-reducing film prepared by the preparation method in any one of the above.
[0021] Compared with the prior art, the application has the following beneficial effects: The application adopts antioxidant and CTAB-montmorillonite modified TPU to form a base film, the antioxidant is connected with the molecular chain of TPU through covalent bond, can capture alkyl free radicals generated during TPU aging, thereby delaying the aging process of TPU, the lamellar structure of CTAB-montmorillonite is anchored between the molecular chains of TPU through physical entanglement, hinders the slipping of the molecular chains of TPU, absorbs and disperses the tensile stress received, reduces the generation of microcracks, and improves the strength and aging resistance of the material; the block copolymerization method is adopted to prepare a block prepolymer containing benzene rings and siloxane segments, the benzene rings are introduced into the molecular chain as rigid structures, which can improve the heat resistance and strength of the prepolymer, and the siloxane segments improve the surface contact angle of the prepolymer, thereby reducing the surface energy of the material and improving the ultraviolet resistance and drag-reducing performance of the material; the application adopts a hot roller pressing method to form microstructures on the surface layer of the drag-reducing film, the microstructures can lift small vortices near the wall surface away from the wall surface, thereby achieving the purpose of reducing frictional resistance; the adhesive of the application contains maleic anhydride grafted SEBS, the maleic anhydride grafted SEBS enhances the interfacial bonding strength in the form of physical entanglement and chemical bonding, improves the peeling strength of the material, and improves the strength and heat resistance of the material. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. The terms used in the embodiments are used for describing specific specific embodiments, rather than limiting the protection scope of the present application. The amount used in the embodiments is a laboratory small test, which can be scaled up proportionally. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor are within the protection scope of the present application.
[0023] Isocyanate-terminated TPU prepolymer (Mn=2000, NCO content: 4.5wt%), nano-titanium dioxide (particle size: 50nm, specific surface area: 200m 2 / g), nano-silicon dioxide (particle size: 30nm, specific surface area: 200m 2 / g), CTAB-montmorillonite (particle size D50: 40μm, interlayer spacing: 1.5nm, density: 2.0g / cm3), hydroxyl-terminated polymethylphenylsiloxane (Mw=5000, hydroxyl value: 100mgKOH / g), polytetrahydrofuran ether diol (brand: PTMG-2000, hydroxyl value: 56mgKOH / g), polyethylene glycol monoacrylate (Mw=2000), hydroxyl-terminated polyurethane (Mw=5000, hydroxyl value: 150mgKOH / g), maleic anhydride grafted SEBS (MAH grafting rate: 1.5wt%), polyurethane acrylate (Mw=1000, viscosity: 1000mPa·s), TPU film (thickness: 50μm).
[0024] The preparation method of KH-560 modified titanium dioxide / KH-560 modified silicon dioxide is as follows: 80g of nano-titanium dioxide / nano-silicon dioxide was added to a mixed solution composed of 300mL of ethanol and 100mL of deionized water, and ultrasonic dispersion was carried out at 60℃ for 30min. Then, 8g of silane coupling agent KH-560 was added, and stirring was carried out until uniform. Subsequently, reaction was carried out at 60℃ for 3h. After the reaction was completed, centrifugal separation was carried out, and washing was carried out with deionized water and ethanol. Then, drying was carried out at 80℃ for 12h, thereby obtaining KH-560 modified titanium dioxide / KH-560 modified silicon dioxide.
[0025] Embodiment 1: A preparation method of a high-strength durable drag-reducing film, specifically as follows: Step 1: Under the protection of nitrogen, 80g of isocyanate-terminated TPU prepolymer, 5g of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol was added to 80g of butyl acetate, and dissolution was carried out under the condition of 80℃ and 400rpm magnetic stirring for 30min. Then, 0.8g of catalyst dibutyltin dilaurate was added, and stirring was carried out until uniform. Subsequently, reaction was carried out at 110℃ for 5h. After the reaction was completed, vacuum drying was carried out at 60℃ for 8h, thereby obtaining hindered phenol modified TPU prepolymer; Step 2: Add 85g of hindered phenol-modified TPU prepolymer and 1.5g of polyethylene glycol monoacrylate to a twin-screw extruder. Set the melt temperature to 180℃ and the screw speed to 200rpm. After melt blending for 5min, add 4g of CTAB-montmorillonite and 2g of silane coupling agent KH-550. Increase the speed to 350rpm and continue blending for 10min before extrusion. Add 0.5g of benzoyl peroxide at the end of the extruder. Set the extrusion temperature to 190℃, the screw speed to 200rpm, and the die temperature to 180℃ to obtain a hindered phenol-MMT-TPU base film with a thickness of 50μm. Step 3: Add 600g of hydroxyl-terminated polymethylphenylsiloxane and 400g of polytetrahydrofuran ether diol to a reaction vessel, mix at 60℃ and 100rpm with magnetic stirring for 30min, add 86g of isophorone diisocyanate, heat to 80℃ and react for 4h, after the reaction is complete, cool to 50℃, add 6g of 1,4-butanediol, and react at 70℃ for 3h to obtain silicone-modified TPU prepolymer; Step 4: Add 80g of silicone-modified TPU prepolymer and 8g of KH-560 modified titanium dioxide to a twin-screw extruder. Set the screw speed to 200rpm, the melt temperature to 180℃, and the blending time to 5min. After blending, add 0.8g of antioxidant 1010 and 0.5g of light stabilizer 944. Continue blending for 5min, then extrude and roll the extruder with a die roller. Add 0.5g of benzoyl peroxide at the end of the extruder. The extrusion temperature is 190℃, the screw speed is 200rpm, the die temperature is 180℃, the rolling temperature is 140℃, and the rolling pressure is 0.5MPa to obtain a silicone-modified TPU surface film with a thickness of 40μm. Step 5: Add 60g of hydroxyl-terminated polyurethane, 15g of maleic anhydride-grafted SEBS and 10g of polyurethane acrylate to 50g of tetrahydrofuran, stir magnetically at 100rpm for 30min at 60℃, add 2.5g of KH-560 modified silica and ultrasonically disperse for 10min, cool to 40℃, add 4g of photoinitiator TPO, continue stirring for 15min, finally add 0.8g of antioxidant 1010 and 0.5g of light stabilizer 944 and ultrasonically disperse for 15min to obtain SEBS modified polyurethane adhesive; Step 6: Put the hindered phenol-MMT-TPU base film and the silicone-modified TPU surface layer film into a plasma cleaning device, and introduce argon and oxygen, set the argon flow rate to 15 sccm, the oxygen flow rate to 5 sccm, the plasma power to 100 W, and the cleaning time to 60 s, after cleaning, coat the SEBS-modified polyurethane adhesive on the hindered phenol-MMT-TPU base film, dry at 80℃ for 15 min to form a 20 μm thick adhesive layer, cover the silicone-modified TPU surface layer film on the adhesive layer and hot-press composite, set the hot-press temperature to 120℃, the hot-press pressure to 0.5 MPa, and the hot-press time to 10 min, after hot-pressing, irradiate with 365 nm UV light, and perform photo-thermal synergistic curing at 120℃ for 15 min, to obtain a high-strength durable drag-reducing film.
[0026] Example 2: A method for preparing a high-strength durable drag-reducing film, specifically: Step 1: Under nitrogen protection, add 85 g of isocyanate-terminated TPU prepolymer and 7 g of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol into 90 g of butyl acetate, dissolve under 80℃, 400 rpm magnetic stirring for 30 min, add 0.8 g of catalyst dibutyltin dilaurate, stir uniformly, and react at 110℃ for 5 h, after the reaction is completed, vacuum dry at 60℃ for 8 h to obtain a hindered phenol-modified TPU prepolymer; Step 2: Add 80 g of hindered phenol-modified TPU prepolymer and 2 g of polyethylene glycol monoacrylate into a twin-screw extruder, set the melting temperature to 180℃, and the screw rotation speed to 200 rpm, melt blend for 5 min, then add 5 g of CTAB-montmorillonite and 2 g of silane coupling agent KH-550, increase the rotation speed to 350 rpm, continue to blend for 10 min, and extrude, add 0.5 g of dibenzoyl peroxide at the end of the extruder, set the extrusion temperature to 190℃, the screw rotation speed to 200 rpm, and the die temperature to 180℃, to obtain a hindered phenol-MMT-TPU base film with a thickness of 50 μm; Step 3: Add 600 g of hydroxyl-terminated polymethylphenylsiloxane and 400 g of polytetramethylene ether glycol into a reaction kettle, mix under 60℃, 100 rpm magnetic stirring for 30 min, add 86 g of isophorone diisocyanate, and react at 80℃ for 4 h, after the reaction is completed, cool to 50℃, add 6 g of 1,4-butanediol, and react at 70℃ for 3 h to obtain a silicone-modified TPU prepolymer; Step 4: 75 g of silicone-modified TPU prepolymer and 10 g of KH-560 modified titanium dioxide were added to a twin-screw extruder, the screw rotation speed was set to 200 rpm, the melting temperature was 180°C, and the blending time was 5 min. After blending, 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944 were added, and the blending was continued for 5 min before extrusion and rolling with a die roller. At the end of the extruder, 0.5 g of dibenzoyl peroxide was added, the extrusion temperature was 190°C, the screw rotation speed was 200 rpm, the die temperature was 180°C, the rolling temperature was 140°C, and the rolling pressure was 0.5 MPa. A silicone-modified TPU surface film with a thickness of 50 μm was obtained. Step 5: 55 g of hydroxyl-terminated polyurethane, 20 g of maleic anhydride-grafted SEBS, and 10 g of polyurethane acrylate were added to 60 g of tetrahydrofuran, stirred at 60°C and 100 rpm for 30 min, 3.0 g of KH-560 modified silica was added and ultrasonically dispersed for 10 min, cooled to 40°C, 4 g of photoinitiator TPO was added, and stirring was continued for 15 min. Finally, 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944 were added and ultrasonically dispersed for 15 min to obtain a SEBS-modified polyurethane adhesive. Step 6: The hindered phenol-MMT-TPU base film and the silicone-modified TPU surface film were placed in a plasma cleaning device, argon and oxygen were introduced, the argon flow was set to 15 sccm, the oxygen flow was set to 5 sccm, the plasma power was set to 100 W, and the cleaning time was set to 60 s. After cleaning, the SEBS-modified polyurethane adhesive was coated on the hindered phenol-MMT-TPU base film, dried at 80°C for 15 min to form a 20 μm thick adhesive layer, and the silicone-modified TPU surface film was overlaid on the adhesive layer and hot-pressed to form a high-strength durable drag-reducing film. The hot-pressing temperature was set to 120°C, the hot-pressing pressure was set to 0.5 MPa, and the hot-pressing time was set to 10 min. After hot-pressing, the film was irradiated with 365 nm UV light and heat-cured at 120°C for 15 min.
[0027] Example 3: A method for preparing a high-strength durable drag-reducing film, specifically: Step 1: Under nitrogen protection, 80 g of isocyanate-terminated TPU prepolymer and 5 g of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were added to 80 g of butyl acetate, dissolved at 80°C and 400 rpm magnetic stirring for 30 min, 0.8 g of catalyst dibutyltin dilaurate was added, stirred uniformly, and reacted at 110°C for 5 h. After reaction, vacuum drying was carried out at 60°C for 8 h to obtain a hindered phenol-modified TPU prepolymer. Step 2: Add 75g of hindered phenol-modified TPU prepolymer and 2.5g of polyethylene glycol monoacrylate to a twin-screw extruder. Set the melt temperature to 180℃ and the screw speed to 200rpm. After melt blending for 5min, add 6g of CTAB-montmorillonite and 2g of silane coupling agent KH-550. Increase the speed to 350rpm and continue blending for 10min before extrusion. Add 0.5g of benzoyl peroxide at the end of the extruder. Set the extrusion temperature to 190℃, the screw speed to 200rpm, and the die temperature to 180℃ to obtain a hindered phenol-MMT-TPU base film with a thickness of 50μm. Step 3: Add 600g of hydroxyl-terminated polymethylphenylsiloxane and 400g of polytetrahydrofuran ether diol to a reaction vessel, mix at 60℃ and 100rpm with magnetic stirring for 30min, add 86g of isophorone diisocyanate, heat to 80℃ and react for 4h, after the reaction is complete, cool to 50℃, add 6g of 1,4-butanediol, and react at 70℃ for 3h to obtain silicone-modified TPU prepolymer; Step 4: Add 70g of silicone-modified TPU prepolymer and 10g of KH-560 modified titanium dioxide to a twin-screw extruder. Set the screw speed to 200rpm, the melt temperature to 180℃, and the blending time to 5min. After blending, add 0.8g of antioxidant 1010 and 0.5g of light stabilizer 944. Continue blending for 5min, then extrude and roll the extruder with a die roller. Add 0.5g of benzoyl peroxide at the end of the extruder. Set the extrusion temperature to 190℃, the screw speed to 200rpm, the die temperature to 180℃, the rolling temperature to 140℃, and the rolling pressure to 0.5MPa to obtain a silicone-modified TPU surface film with a thickness of 50μm. Step 5: Add 50g of hydroxyl-terminated polyurethane, 20g of maleic anhydride-grafted SEBS and 15g of polyurethane acrylate to 60g of tetrahydrofuran, stir magnetically at 100rpm for 30min at 60℃, add 3.5g of KH-560 modified silica and ultrasonically disperse for 10min, cool to 40℃, add 4g of photoinitiator TPO, continue stirring for 15min, finally add 0.8g of antioxidant 1010 and 0.5g of light stabilizer 944 and ultrasonically disperse for 15min to obtain SEBS modified polyurethane adhesive; Step 6: Put the hindered phenol-MMT-TPU base film and the silicone-modified TPU surface layer film into a plasma cleaning device, and introduce argon and oxygen, set the argon flow rate to 15 sccm, the oxygen flow rate to 5 sccm, the plasma power to 100 W, and the cleaning time to 60 s. After cleaning, apply the SEBS-modified polyurethane adhesive to the hindered phenol-MMT-TPU base film, dry at 80°C for 15 min to form a 25-μm-thick adhesive layer, cover the silicone-modified TPU surface layer film on the adhesive layer, and hot-press composite, set the hot-press temperature to 120°C, the hot-press pressure to 0.5 MPa, and the hot-press time to 10 min. After hot-pressing, irradiate with 365 nm UV light, and perform photo-thermal synergistic curing at 120°C for 15 min to obtain a high-strength durable drag-reducing film.
[0028] Based on Example 1, the following comparative experiments are performed, specifically Comparative Example 1, Comparative Example 2, and Comparative Example 3, as described below. Comparative Example 1: This comparative example relates to a method for preparing a high-strength durable drag-reducing film, which differs from Example 1 in that the TPU base film is not modified, specifically: Step 1: Put 600 g of hydroxyl-terminated polymethylphenylsiloxane and 400 g of polytetramethylene ether glycol into a reaction kettle, mix at 60°C and 100 rpm for 30 min, add 86 g of isophorone diisocyanate, and raise the temperature to 80°C for 4 h. After the reaction is completed, lower the temperature to 50°C, add 6 g of 1,4-butanediol, and react at 70°C for 3 h to obtain a silicone-modified TPU prepolymer; Step 2: Put 80 g of the silicone-modified TPU prepolymer and 8 g of KH-560-modified titanium dioxide into a twin-screw extruder, set the screw rotation speed to 200 rpm and the melting temperature to 180°C, and blend for 5 min. After blending is completed, add 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944, continue blending for 5 min, and then extrude and roll with a mold roller. At the end of the extruder, add 0.5 g of dibenzoyl peroxide, set the extrusion temperature to 190°C, the screw rotation speed to 200 rpm, the die temperature to 180°C, the rolling temperature to 140°C, and the rolling pressure to 0.5 MPa to obtain a silicone-modified TPU surface layer film with a thickness of 40 μm; Step 3: Put 60 g of hydroxyl-terminated polyurethane, 15 g of maleic anhydride-grafted SEBS, and 10 g of polyurethane acrylate into 50 g of tetrahydrofuran, mix at 60°C and 100 rpm for 30 min, add 2.5 g of KH-560-modified silica and ultrasonically disperse for 10 min, lower the temperature to 40°C, add 4 g of a photoinitiator TPO, and continue stirring for 15 min. Finally, add 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944 and ultrasonically disperse for 15 min to obtain an SEBS-modified polyurethane adhesive; Step 4: Put the TPU film and the silicone-modified TPU surface layer film into a plasma cleaning device, and pass in argon and oxygen, set the argon flow rate to 15 sccm, the oxygen flow rate to 5 sccm, the plasma power to 100 W, and the cleaning time to 60 s, after cleaning, coat the SEBS-modified polyurethane adhesive on the TPU film, dry at 80℃ for 15 min to form a 20 μm thick adhesive layer, cover the silicone-modified TPU surface layer film on the adhesive layer and hot-press composite, set the hot-press temperature to 120℃, the hot-press pressure to 0.5 MPa, and the hot-press time to 10 min, after hot-pressing, irradiate with 365 nm UV light, and perform photo-thermal synergistic curing at 120℃ for 15 min, to obtain a high-strength durable drag-reducing film.
[0029] Comparative Example 2: This comparative example relates to a method for preparing a high-strength durable drag-reducing film, which is different from Example 1 in that the TPU surface layer film is not modified, specifically: Step 1: Under nitrogen protection, add 80 g of isocyanate-terminated TPU prepolymer and 5 g of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol into 80 g of butyl acetate, dissolve under 80℃, 400 rpm magnetic stirring for 30 min, add 0.8 g of catalyst dibutyltin dilaurate, stir uniformly, and react at 110℃ for 5 h, after the reaction is completed, vacuum dry at 60℃ for 8 h to obtain a hindered phenol-modified TPU prepolymer; Step 2: Add 85 g of hindered phenol-modified TPU prepolymer and 1.5 g of polyethylene glycol monoacrylate into a twin-screw extruder, set the melting temperature to 180℃, and the screw rotation speed to 200 rpm, melt blend for 5 min, then add 4 g of CTAB-montmorillonite and 2 g of silane coupling agent KH-550, increase the rotation speed to 350 rpm, and continue to blend for 10 min for extrusion, add 0.5 g of dibenzoyl peroxide at the end of the extruder, set the extrusion temperature to 190℃, the screw rotation speed to 200 rpm, and the die temperature to 180℃, to obtain a hindered phenol-MMT-TPU base film with a thickness of 50 μm; Step 3: Add 60 g of hydroxyl-terminated polyurethane, 15 g of maleic anhydride grafted SEBS, and 10 g of polyurethane acrylate into 50 g of tetrahydrofuran, stir at 60℃ and 100 rpm for 30 min, add 2.5 g of KH-560 modified silica and ultrasonic dispersion for 10 min, cool to 40℃, add 4 g of photoinitiator TPO and continue to stir for 15 min, finally add 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944 and ultrasonic dispersion for 15 min, to obtain a SEBS-modified polyurethane adhesive; Step 4: Put the hindered phenol-MMT-TPU base film and TPU film into the plasma cleaning equipment, and input argon and oxygen, set the argon flow rate to 15 sccm, the oxygen flow rate to 5 sccm, the plasma power to 100 W, and the cleaning time to 60 s. After cleaning, coat the SEBS modified polyurethane adhesive on the hindered phenol-MMT-TPU base film, dry at 80℃ for 15 min to form a 20 μm thick adhesive layer, roll the TPU film at 140℃ with a mold roll to form a TPU surface layer film covering the adhesive layer and hot-press composite, set the hot-press temperature to 120℃, the hot-press pressure to 0.5 MPa, and the hot-press time to 10 min. After hot-pressing, irradiate with 365 nm UV light, and perform photo-thermal synergistic curing at 120℃ for 15 min to obtain a high-strength durable drag-reducing film.
[0030] Comparative Example 3: This comparative example relates to a method for preparing a high-strength durable drag-reducing film, which differs from Example 1 in that a polyurethane adhesive is used, specifically: Step 1: Under nitrogen protection, add 80 g of isocyanate-terminated TPU prepolymer and 5 g of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol to 80 g of butyl acetate, dissolve under 80℃, 400 rpm magnetic stirring for 30 min, add 0.8 g of catalyst dibutyltin dilaurate, stir uniformly, and react at 110℃ for 5 h. After the reaction is completed, vacuum dry at 60℃ for 8 h to obtain a hindered phenol-modified TPU prepolymer; Step 2: Add 85 g of hindered phenol-modified TPU prepolymer and 1.5 g of polyethylene glycol monoacrylate to a twin-screw extruder, set the melting temperature to 180℃, and the screw speed to 200 rpm. After melting and blending for 5 min, add 4 g of CTAB-montmorillonite and 2 g of silane coupling agent KH-550, increase the speed to 350 rpm, and continue to blend for 10 min. Extrude at an extruder temperature of 190℃, a screw speed of 200 rpm, and a die temperature of 180℃ to obtain a hindered phenol-MMT-TPU base film; Step 3: Add 600 g of hydroxyl-terminated polymethylphenylsiloxane and 400 g of polytetramethylene ether glycol to a reaction kettle, mix at 60℃, 100 rpm magnetic stirring for 30 min, add 86 g of isophorone diisocyanate, and react at 80℃ for 4 h. After the reaction is completed, cool to 50℃, add 6 g of 1,4-butanediol, and react at 70℃ for 3 h to obtain a silicone-modified TPU prepolymer; Step 4: 80 g of silicone-modified TPU prepolymer and 8 g of KH-560 modified titanium dioxide were added to a twin-screw extruder, the screw rotation speed was set to 200 rpm, the melting temperature was 180°C, the blending time was 5 min, after blending, 0.8 g of antioxidant 1010 and 0.5 g of light stabilizer 944 were added, and the blending was continued for 5 min, then extruded and rolled with a die roller, 0.5 g of dibenzoyl peroxide was added at the end of the extruder, the extrusion temperature was 190°C, the screw rotation speed was 200 rpm, the die temperature was 180°C, the rolling temperature was 140°C, the rolling pressure was 0.5 MPa, and a silicone-modified TPU surface film was obtained; Step 5: The hindered phenol-MMT-TPU base film and the TPU film were placed in a plasma cleaning device, argon and oxygen were introduced, the argon flow was set to 15 sccm, the oxygen flow was set to 5 sccm, the plasma power was set to 100 W, and the cleaning time was set to 60 s, after cleaning, a polyurethane adhesive was coated on the hindered phenol-MMT-TPU base film, dried at 80°C for 15 min to form a 20 μm thick adhesive layer, and the silicone-modified TPU surface film was covered on the adhesive layer and hot-pressed to form a composite, the hot-pressing temperature was set to 120°C, the hot-pressing pressure was set to 0.5 MPa, and the hot-pressing time was set to 10 min, after hot-pressing, 365 nm UV light was irradiated, and the light-heat synergistic curing was carried out at 120°C for 15 min, and a high-strength durable drag-reducing film was obtained.
[0031] Detection experiment: High-strength durable drag-reducing film test samples were prepared according to each embodiment and comparative example, and tensile strength test, interlayer shear strength test and weather resistance test were carried out.
[0032] Tensile strength test: the tensile strength test of the drag-reducing film was carried out according to "Determination of tensile properties of plastics - Part 3: test conditions for films and sheets" (GB / T 1040.3-2006), five dumbbell-shaped samples (total length of 150 mm, width of 25 mm, length of narrow parallel part of 33 mm, width of narrow parallel part of 6 mm, gauge length of 25 mm) were cut from the drag-reducing film test sample, the two ends of the sample were clamped and fixed with the upper and lower clamps of the tensile testing machine, the testing machine was started, and the sample was stretched at a tensile rate of 50 mm / min until the sample was broken, the maximum load and the elongation at break were recorded, the tensile strength of the sample was calculated, and the test results were averaged.
[0033] Interlaminar shear strength test: 5 dumbbell-shaped samples (total sample length 150 mm, sample width 25 mm, narrow parallel part length 33 mm, narrow parallel part width 6 mm, gauge length 25 mm) are cut from the drag reduction film test sample, the two ends of the sample are fixed with the clamps of the tensile testing machine, the shear zone (narrow part in the middle of the sample) is aligned with the center of the clamp, the testing machine is started, the loading rate is set to 2 mm / min, the load-displacement curve is recorded, and the test is stopped after the sample interface is damaged (slippage or delamination) occurs, the interlaminar shear strength of the sample is calculated, and the test results are averaged.
[0034] Weather resistance test: The weather resistance test of the drag reduction film refers to "Plastics - Methods of exposure to laboratory light sources - Part 3: Fluorescent UV lamps" (GB / T 16422.3-2022). 10 dumbbell-shaped samples (total sample length 150 mm, sample width 25 mm, narrow parallel part length 33 mm, narrow parallel part width 6 mm, gauge length 25 mm) are cut from the drag reduction film test sample, 5 of which are randomly selected for tensile strength testing, the test results are averaged, and the remaining 5 are placed in an ultraviolet aging test box. The temperature in the aging box is 60°C, the irradiation light source is 365nm ultraviolet light, the irradiation intensity is 0.89W / m 2 , after aging for 500h, the tensile strength after aging is measured, the test results are averaged, and the tensile strength retention rate of the sample is calculated.
[0035]
[0036] Conclusion: From the test data, it can be seen that compared with the test results of the comparative examples, the tensile strength, interlaminar shear strength and tensile strength retention rate of the high-strength durable drag reduction film provided by the examples are all better than those of the comparative examples. The high-strength durable drag reduction film prepared by the examples has good strength and durability, and can solve the problems of insufficient strength and poor durability of the drag reduction film.
[0037] It is apparent to those skilled in the art that the present application is not limited to the details of the foregoing exemplary embodiments, and that the present application can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered in all respects as illustrative and not restrictive, and the scope of the present application is defined by the appended claims rather than the foregoing description, and it is intended to encompass all changes falling within the meaning and range of equivalents of the claims.
Claims
1. A method of making a high-strength durable drag-reducing film, characterized by: Specifically: Step 1: prepare a hindered phenol modified TPU prepolymer using 3,5-di-tert-butyl-4-hydroxybenzyl alcohol and an isocyanate-terminated TPU prepolymer, and blend and extrude with CTAB-montmorillonite to prepare a hindered phenol-MMT-TPU base film; Step 2: prepare a silicone modified TPU prepolymer using a hydroxyl-terminated polymethylphenylsiloxane, a polytetramethylene ether glycol, and isophorone diisocyanate, and blend and extrude with KH-560 modified titanium dioxide to prepare a silicone modified TPU surface film; Step 3: after plasma cleaning of the hindered phenol-MMT-TPU base film and the silicone modified TPU surface film, prepare a SEBS modified polyurethane adhesive using a hydroxyl-terminated polyurethane and maleic anhydride grafted SEBS, coat it on the hindered phenol-MMT-TPU base film and dry it, form an adhesive layer, and then hot press the silicone modified TPU surface film to obtain a high-strength durable drag-reducing film after light-heat synergistic curing treatment.
2. The method for preparing a high-strength, durable drag-reducing membrane according to claim 1, characterized in that: The preparation method of the hindered phenol-MMT-TPU base film is as follows: Under nitrogen protection, the isocyanate-terminated TPU prepolymer and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol are added to butyl acetate, dissolved under magnetic stirring at 80-90℃ and 300-400rpm for 30-40min, a catalyst dibutyltin dilaurate is added, stirred uniformly, and reacted at 110-120℃ for 4-5h. After the reaction is completed, vacuum drying is performed at 60-70℃ for 6-8h to obtain the hindered phenol modified TPU prepolymer. The hindered phenol modified TPU prepolymer and polyethylene glycol monoacrylate are added to a twin-screw extruder, the melting temperature is set to 170-180℃, the screw rotation speed is 150-200rpm, and after melting and blending for 3-5min, CTAB-montmorillonite and silane coupling agent KH-550 are added, the rotation speed is increased to 300-350rpm, and the blending is continued for 5-10min to extrude. At the end of the extruder, dibenzoyl peroxide is added, the extrusion temperature is 180-190℃, the screw rotation speed is 200-250rpm, and the die temperature is 170-180℃ to obtain the hindered phenol-MMT-TPU base film.
3. The method for preparing a high-strength, durable drag-reducing membrane according to claim 2, characterized in that: The mass ratio of the isocyanate-terminated TPU prepolymer, 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, and butyl acetate is (80-90):(5-10):(80-100), and the mass of dibutyltin dilaurate is 0.8-1.5wt% of the mass of the isocyanate-terminated TPU prepolymer.
4. The method for preparing a high-strength, durable drag-reducing membrane according to claim 2, characterized in that: In terms of mass parts, the hindered phenol-MMT-TPU base film includes 75-85 parts of the hindered phenol modified TPU prepolymer, 1.5-2.5 parts of polyethylene glycol monoacrylate, 4-6 parts of CTAB-montmorillonite, 1-3 parts of silane coupling agent KH-550, and 0.5-1 part of dibenzoyl peroxide. The thickness of the hindered phenol-MMT-TPU base film is 30-50μm.
5. The method for preparing a high-strength, durable drag-reducing membrane according to claim 1, characterized in that: The preparation method of the silicone modified TPU surface film is as follows: Put the hydroxyl-terminated polymethylphenylsiloxane, polytetrahydrofuran ether diol into the reaction kettle, 60-70℃, 100-150rpm magnetic stirring mixed 20-30min, add isophorone diisocyanate, temperature to 80-90℃ reaction 3-4h, after the reaction is completed, cooling to 40-50℃, add 1,4-butanediol, 70-80℃ reaction 2-3h, get silicone modified TPU prepolymer; Put the silicone modified TPU prepolymer and KH-560 modified titanium dioxide into the twin screw extruder, set the screw speed to 200-250rpm, the melt temperature to 170-180℃, the blending time to 3-5min, after the blending is completed, add antioxidant 1010 and light stabilizer 944, continue to blend for 5-10min, then extrude and roll with the mold roller, add dibenzoyl peroxide at the end of the extruder, the extrusion temperature is 180-190℃, the screw speed is 200-250rpm, the die temperature is 170-180℃, the rolling temperature is 130-140℃, the rolling pressure is 0.3-0.5MPa, get the silicone modified TPU surface film.
6. The method of claim 5, wherein the high strength durable drag reducing film is prepared by the steps of: The mass ratio of hydroxyl-terminated polymethylphenylsiloxane, polytetrahydrofuran ether diol, isophorone diisocyanate and 1,4-butanediol is (60-70):(40-50):(8.5-9.5):(0.6-1.0).
7. The method for preparing a high-strength, durable drag-reducing membrane according to claim 5, characterized in that: According to mass parts, the silicone modified TPU surface film includes: 70-80 parts of silicone modified TPU prepolymer, 8-12 parts of KH-560 modified titanium dioxide, 0.8-1.2 parts of antioxidant 1010, 0.5-0.7 parts of light stabilizer 944, 0.5-1 parts of dibenzoyl peroxide; the thickness of the silicone modified TPU surface film is 30-50μm.
8. The method for preparing a high-strength, durable drag-reducing membrane according to claim 1, characterized in that: The preparation method of the SEBS modified polyurethane adhesive is: Put the hydroxyl-terminated polyurethane, maleic anhydride grafted SEBS and polyurethane acrylate into tetrahydrofuran, 60-70℃, 100-150rpm magnetic stirring 20-30min, add KH-560 modified silica and ultrasonic dispersion for 5-10min, cooling to 30-40℃, add photoinitiator TPO, continue to stir for 10-20min, finally add antioxidant 1010 and light stabilizer 944 and ultrasonic dispersion for 15-20min, get the SEBS modified polyurethane adhesive.
9. The method for preparing a high-strength, durable drag-reducing membrane according to claim 8, characterized in that: According to mass parts, the SEBS modified polyurethane adhesive includes: 50-60 parts of hydroxyl-terminated polyurethane, 15-20 parts of maleic anhydride grafted SEBS, 10-15 parts of polyurethane acrylate, 50-60 parts of tetrahydrofuran, 2.5-3.5 parts of KH-560 modified silica, 4-6 parts of photoinitiator TPO, 0.8-1.2 parts of antioxidant 1010, 0.5-0.7 parts of light stabilizer 944.
10. A high strength durable drag reducing film characterized by: Prepared by the preparation method of any one of claims 1-9. Prepared by the preparation method of any one of claims 1-9.
Citation Information
Patent Citations
Hot-stamping preparation method of Al layer coating type TPU (thermoplastic polyurethane) film friction reduction micro-groove for airship skin
CN102673052A
Micro-groove anti-drag flexible film and preparation method thereof
CN110484151A
Long-acting, stable, flexible, impact-resistant and resistance-reducing protective film and preparation process thereof
CN120923842A
Ultraviolet aging resistant anti-drag film and preparation process thereof
CN120963181A
Coextrusion die and system, method of making coextruded articles and coextruded articles made thereby
US20120263906A1
Cited By
Polypropylene mute pipe
CN122100632A